IS Application Capabilities and Relational Value in Interfirm Partnerships - Saraf, Nilesh; Langdon, Christoph Schlueter; Gosain, Sanjay (Information Systems Research, 2007)
This study examines how capabilities of information systems (IS) applications deployed in the context of interfirm relationships contribute to business performance. We propose that these capabilities augment the relational value that a firm derives from its business partners—channel partners and customer enterprises—in the context of the distribution channel. Two cospecialized relational assets are considered as key to realization of relational value—knowledge sharing and process coupling. Hypotheses linking two IS capabilities (IS flexibility and IS integration) to the relational asset dimensions, and ultimately to firm performance, are proposed. The research model is tested based on data collected through a survey of business units of enterprises embedded in customer and channel partner ties in the high-tech and financial services industries. We find that IS integration with channel partners and customers contributes to both knowledge sharing and process coupling with both types of enterprise partners, whereas IS flexibility is a foundational capability that indirectly contributes to value creation in interfirm relationships by enabling greater IS integration with partner firms. We find that two types of relational assets are significantly associated with business performance—knowledge sharing with channel partners and process coupling with customers—pointing to underlying mechanisms that differentially leverage resources of different types of channel partners. Implications for theory development and practice based on these findings are proposed.